Neoadjuvant Chemoradiotherapy and Surgery for Esophageal Squamous Cell Carcinoma Versus Definitive Chemoradiotherapy With Salvage Surgery as Needed: The Study Protocol for the Randomized Controlled NEEDS Trial - Nilsson, Magnus; Olafsdottir, Halla; Alexandersson von Döbeln, Gabriella; Villegas, Fernanda; Gagliardi, Giovanna; Hellström, Mats; Wang, Qiao-Li; Johansson, Hemming; Gebski, Val; Hedberg, Jakob; Klevebro, Fredrik; Markar, Sheraz; et al. (Frontiers in Oncology, 2022)
Background The globally dominant treatment with curative intent for locally advanced esophageal squamous cell carcinoma (ESCC) is neoadjuvant chemoradiotherapy (nCRT) with subsequent esophagectomy. This multimodal treatment leads to around 60% overall 5-year survival, yet with impaired post-surgical quality of life. Observational studies indicate that curatively intended chemoradiotherapy, so-called definitive chemoradiotherapy (dCRT) followed by surveillance of the primary tumor site and regional lymph node stations and surgery only when needed to ensure local tumor control, may lead to similar survival as nCRT with surgery, but with considerably less impairment of quality of life. This trial aims to demonstrate that dCRT, with selectively performed salvage esophagectomy only when needed to achieve locoregional tumor control, is non-inferior regarding overall survival, and superior regarding health-related quality of life (HRQOL), compared to nCRT followed by mandatory surgery, in patients with operable, locally advanced ESCC. Methods This is a pragmatic open-label, randomized controlled phase III, multicenter trial with non-inferiority design with regard to the primary endpoint overall survival and a superiority hypothesis for the experimental intervention dCRT with regard to the main secondary endpoint global HRQOL one year after randomization. The control intervention is nCRT followed by preplanned surgery and the experimental intervention is dCRT followed by surveillance and salvage esophagectomy only when needed to secure local tumor control. A target sample size of 1200 randomized patients is planned in order to reach 462 events (deaths) during follow-up. Clinical Trial Registration The trial is registered on www.ClinicalTrials.gov, identifier NCT04460352.